FACTORES ASOCIADOS A ANSIEDAD PERINATAL EN PUÉRPERASEN UN CENTRO DE SALUD EN EL AÑO 2020 - Rivera Morales, Mariana (2024)
Introduction. The postpartum period, while a natural biological event, is characterized by significant emotional vulnerability, during which women may face various conflicting experiences. Objective. To determine the factors associated with perinatal anxiety in postpartum women treated at a health center in 2020. Materials and Methods. A quantitative, cross-sectional, analytical, and observational study was conducted. The population consisted of 87 postpartum women treated at the Delicias de Villa Health Center. Sociodemographic, clinical, and obstetric data were collected through a questionnaire, and the Perinatal Anxiety Screening Scale (PASS) was used to measure anxiety. Statistical analysis included Poisson regression to calculate adjusted prevalence ratios, considering statistical significance at a p-value <0,05. Results. The prevalence of perinatal anxiety was 17,24%. Significant factors associated with perinatal anxiety included foreign nationality (aPR: 14,38; 95% CI: 2,34-88,14; p=0,004), while residence in settlements and primiparity showed marginal associations. Conclusion. Being of foreign nationality is significantly associated with a higher risk of perinatal anxiety, highlighting the need for targeted interventions for vulnerable groups in primary care settings.